The Tingkat Kesadahan dan Uji Derajat Keasaman (pH) pada Air Tanah di Desa Mapane Tambu Kecamatan Balaesang Kabupaten Donggala - Ishak Ishak; Minarni Rama Jura; Irwan Said; Sri Hastuti Virgianti Pulukadang (Media Eksakta, 2022)
Research has been carried out on the level of hardness and the degree of acidity (pH) in groundwater in Mapane Tambu Village, Balaesang District, Donggala Regency. The purpose of this study was to determine the concentration of the water hardness level and the degree of acidity of the water, complexometric method was used to determine the level of water hardness using three samples and obtained the results of sample A 15.61 mg/L; sample B 9.40 mg/L and sample C 19.22 mg/L, with a total hardness level obtained an average value of 14.74 mg/L classified in the low hardness category. Then the degree of acidity (pH) was measured using the electrometric method with a (pH) meter with three variations of sample results and the results obtained were sample A 7.713; sample B 8,511; sample C 6.916. The determination of the degree of acidity (pH) of the water obtained in the three samples was in accordance with the regulation of PERMENKES Number 492/Menkes/Per/IV/2010 concerning the quality of clean water which was in the pH range of 6.5 - 6.8